SYSTEMS OF ASPIRATION WITH VORTEX DEDUSTERS TO COUNTERCLAIMS TWIRLED FLOW AS COLLECTIVE MEANS OF PROTECTION OF WORKERS FROM DUST - Natalia Sergeevna Zhukova; Elena Anatolievna Semenova; Denis Valeryevich Azarov; Artem Victorovich Azarov (Современная наука и инновации)
The article is presented various designs of vortex dedusters to counterclaims twirled flow and their characteristics. The ways of improvement of dust removal ability of devices are shown, concerning their constructive elements.